2020
DOI: 10.21203/rs.3.rs-17410/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficient production of myo-inositol in Escherichia coli through metabolic engineering

Abstract: Background The biosynthesis of high value-added compounds through metabolically engineered strains has received widely attention in recent years. As an effective compound in pharmaceutical, cosmetic and food industry, myo-inositol (inositol) is mainly produced via a harsh set of chemical reactions from phytate. The proper distribution of carbon flux between cell growth and inositol production was a major challenge for constructing an efficient inositol-synthetic pathway. Recombinant E. coli strains have been c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 36 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…As G6P is the key node of central metabolism, only a small amount of G6P can be used as the precursor for inositol production. The difference is that the myo ‐inositol biosynthesis of S. cerevisiae is rigorously regulated and controlled, owing to the key enzymes are inhibited by myo ‐inositol and the synthesis of I1P is inhibited by at least three genes of OPI1, OPI2, OPI4, thus the titer of inositol produced by S. cerevisiae is only 9 g/L by OPI1 gene deletion and fermentation optimization, 53 while the titer of inositol produced by E. coli could reach to a high level of 106.3 g/L by synergetic utilization of glucose and glycerol as carbon sources 36 . The synthetic utilization of glucose and glycerol may be a hopeful method for high‐titer of myo‐ inositol production and high‐density fermentation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As G6P is the key node of central metabolism, only a small amount of G6P can be used as the precursor for inositol production. The difference is that the myo ‐inositol biosynthesis of S. cerevisiae is rigorously regulated and controlled, owing to the key enzymes are inhibited by myo ‐inositol and the synthesis of I1P is inhibited by at least three genes of OPI1, OPI2, OPI4, thus the titer of inositol produced by S. cerevisiae is only 9 g/L by OPI1 gene deletion and fermentation optimization, 53 while the titer of inositol produced by E. coli could reach to a high level of 106.3 g/L by synergetic utilization of glucose and glycerol as carbon sources 36 . The synthetic utilization of glucose and glycerol may be a hopeful method for high‐titer of myo‐ inositol production and high‐density fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…It is presumed that the high yield of myo ‐inositol from glucose would not be available on metabolic engineering of strain. However, massive efforts have been devoted recently to improve myo ‐inositol production via the biosynthetic pathway of myo ‐inositol from different substrates 35,36 …”
Section: Microbial Fermentative Production Of Myo‐inositolmentioning
confidence: 99%
See 2 more Smart Citations
“…This knowledge enhances their commercial potential, especially as it pertains to inositol production. A recent research article has demonstrated the complexity involved in engineering inositol production in bacterial cells [ 50 ]. Given the importance of inositol in many industries, including those related to health, pharmaceuticals, and agriculture, information presented here will allow a more efficient production of inositol and an extracellular vesicle in which to transport it.…”
Section: Discussionmentioning
confidence: 99%